Analisis Kejadian Risiko Produksi Kangkung pada Urban Farming (Studi Kasus di Greenhouse X) - Hana, Talitha Ummiyah; Wiyono, Sulistyodewi Nur; Heryanto, Mahra Arari; Tridakusumah, Ahmad Choibar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The risk management process begins with identifying potential risks that may occur in a business. Greenhouse X is an urban farming enterprise in Bandung City whose supply of water spinach (kangkung) has not been able to optimally meet market demand. Greenhouse X also partners with other farmers to help fulfill supply needs, but supplier partners are often inconsistent in meeting supply demands. There are risks in water spinach production that lead to uncertainty in supply quantity, which can harm the business. This research aims to analyze production risk events in hydroponic water spinach at Greenhouse X and its supplier partners. The study uses a qualitative design with a case study method analyzed descriptively. The results identify 19 production risk events with varying severity levels. The highest-risk events with a serious impact (Si=9) are plant death during growth and root rot. Other high-impact risks include harvest delays and unmet product quantity were identified as having extreme impacts (Si=8).